عہد وسطی میں مسلمانوں کا سائنسی نصاب اور سائنسی ترقی میں اس کا کردار: The scientific curriculum of Muslims during medieval period and its rule in the scientific development - Dr. Syed Abdul Rasheed (MEI, 2023)
This article discusses one of the main reasons for the scientific development of Muslims during medieval period. It is stated in the article that a specific curriculum of science played an important role behind rise of scientific development. The article introduces a curriculum of mathematics and astronomy, which was divided into three levels, in the first level the textbook of mathematics was Uqleedas or the Book of Euclid, at the last level the textbook of astronomy was Majisti or Almagest, with a number of books taught in between. The article presents a detailed study of this curriculum and mentions translations and commentaries of these book as well as mentions the impact of this curriculum on the later period.